Identifikasi Aksi Terorisme di Indonesia: Identification of Terrorism Actions in Indonesia - Achluddin Ibnu Rochim; Ute Chairuz Mochamad Nasution; Eddy Wahyudi (Society, 2023)
The threat of terrorism in Indonesia is not a new phenomenon but has persisted since the early years of independence. Presently, perpetrators of terrorism come from various groups with diverse motives, encompassing ideology, politics, and security disturbances. This study aims to delineate the profile, characteristics, and motives of terrorism in Indonesia. Employing a descriptive research method with a qualitative approach, data collection involved non-participant observation. The findings reveal that from 2017 to 2022, there were 97 recorded instances of terrorism actions in Indonesia. Political motives predominantly drove these actions, constituting 88 cases. Moreover, the targets of terrorist actions exhibited minimal disparity between non-civilian and civilian objects, with 59 and 38 cases, respectively. The terrorism action networks are primarily associated with Jamaah Ansharut Daulah (69 cases), East Indonesia Mujahideen (10 cases), and Lone Wolf operatives (7 cases). The study’s findings highlight the role of political factors in terrorist activities in Indonesia, informing policymakers and law enforcement agencies about the need for targeted interventions to address underlying grievances and enhance social cohesion. Furthermore, identifying terrorist networks offers valuable intelligence for disrupting these groups, ultimately improving national security and public safety.